In the Pocket of the Underground Paradoxalist - Бержайте, Дагне; Киселюте, Ингрида (Literatūra, 2016)
For many years, the F. Dostoyevsky researchers have been arguing about the function of money in the writer’s works. The majority of the Dostoyevsky specialists maintain that, even though the material issue remains urgent in all Dostoevsky’s works, it does not determine the characters’ attitudes and behavior. In order to refute this conventional opinion, the authors of the article have applied some of the most important aspects (Production, Internal Circulation, Metatheoretical) of the New Economic Criticism, a new method of literary analysis, originated a few decades ago in the United States, and also discuss various aspects of money as the economic category of Dostoyevsky’s works. The article is focused on the Notes from Underground, one of the most important novels of Dostoyevsky, written in the full swing of the incipient yet extensive reforms of the mid-19th century Russia. The article seeks to demonstrate that the economic practices of the main character not only determine the entire course of the story, but also reflect the essential principles of the Russian economic system functioning and its further change as well as help to reveal the meanings of the text no longer being recognized today.